Answer :


Using the splitting middle term - the middle term of the general equation is divided in two such values that:


Product = a.c


For the given equation a = 2; b = 1; c = -6


= 2. - 6


= - 12


And either of their sum or difference = b


= 1


Thus the two terms are 4 and - 3


Difference = 4 - 3 = 1


Product = 4. - 3 = - 12




2x(x + 2)-3(x + 2) = 0


(2x-3)(x + 2) = 0


(2x-3) = 0 or (x + 2) = 0


x = 3/2, x = -2


Roots of equation are 3/2, - 2


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Which of the follRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics